Assessing the reactivity of sodium alkyl-magnesiates towards quinoxaline: single electron transfer (SET) vs. nucleophilic alkylation processes. Issue 14 (30th November 2015) - Livingstone, Zoe; Hernán-Gómez, Alberto; Baillie, Sharon E.; Armstrong, David R.; Carrella, Luca M.; Clegg, William; Harrington, Ross W.; Kennedy, Alan R.; Rentschler, Eva; Hevia, Eva
Abstract : Structurally tracking the reaction of a sodium butylmagnesiate supported by a bulky silyl(bisamide) ligand towards quinoxaline, SET reactivity. Abstract : By exploring the reactivity of sodium butyl-magnesiate (1 ) supported by the bulky chelating silyl(bisamido) ligand Ph2 Si(NAr*)2 2− (Ar* = 2, 6-iPr2 -C6 H3 ) towards Quinoxaline (Qx ), the ability of this bimetallic system to effectively promote SET processes has been disclosed. Thus1 executes the single-electron reduction ofQx affording complex (2 ) whose structure in the solid state contains two quinaxolyl radical anionsQx ˙ stabilised within a dimeric magnesiate framework. Combining multinuclear NMR and EPR measurements with DFT calculations, new insights into the constitution of2 in solution and its magnetic behaviour have been gained. Further evidence on the SET reactivity of1 was found when it was reacted with nitroxyl radical TEMPO which furnished contacted ion pair sodium magnesiate [(Ph2 Si(NAr*)2 )Mg(TEMPO − )Na(THF)3 ] (4 ) where both metals are connected by an alkoxide bridge, resulting from reduction of TEMPO. The role that the different ligands present in1 can play in these new SET reactions has also been assessed. Using an amination approach, the Bu group in1 can be replaced by the more basic amide TMP allowing the isolation of (3 ) which was characterised by multinuclear NMR and X-ray crystallography. 1 H NMR monitoring of the reaction of3 withQx showed its conversion to2, leaving the hydrogen atoms of the heterocycle untouched. Contrastingly, using sodium homoalkyl magnesiate [NaMg(CH2 SiMe3 )3 ] (5 ) led to the chemoselective C2 alkylation of this heterocycle, suggesting that the presence of the steric stabiliser Ph2 Si(NAr*)2 2− on the mixed-metal reagent is required in order to facilitate theQx reduction.